Evaluation of Tall Fescue Cultivars - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
Stand frequency in spring 2014 was higher for ‘AU Triumph’ than for ‘AGRFA-111’ and ‘BarOptima Plus E34.’ Spring 2014 yield was higher for ‘Jesup MaxQ’ and ‘Texoma MaxQ II’ than for 10 of the 17 other entries. Fall production was greater for ‘AGRFA- 111’ and ‘Bar FA80 DH’ than for 13 other entries. Total 2014 production was higher for ‘Texoma MaxQ II’ than for five other cultivars. Total 4-year forage production was greater for ‘Texoma MaxQ II’ and ‘Martin 2 647’ than for the seven below-average entries. ‘Bariane’ and ‘AGRFA-179’ were lower than for six of the highest-yielding entries.
Keywords: fescue endophyte; stand persistence; multi-year production